Using Building Information Modelling (BIM) by studying building orientation during design to achieve more sustainable buildings - Jamal Younis Omran; Moustafa Ali Wassouf (Vestnik MGSU)
Introduction. Energy is one of the most important issues that attract the attention of the whole world, and this in turn is reflected in the increase in energy consumption in residential and industrial buildings Therefore, the process of assessing the efficiency and quality of interior spaces is an important step from which the process of developing and upgrading these spaces begins to reach a sustainable model from an environmental, economic and social point of view.Materials and methods. The research aims to study the distribution patterns of residential divisions and their reflection on the energy of a residential suburb consisting of twenty residential buildings in Tartous Governorate, through the development of a software tool using Dynamo, which is one of the visual programming methods used in (BIM) using a programming language (Python) with the addition of studying heating and air conditioning loads for current orientation with comparison with loads after directing the building at different angles in order to reduce consumption and benefit from solar radiation sources through Revit. An analytical approach was used, through the analysis and extrapolation of the literature and references related to the study, in addition to the deductive approach by deducing problems in the current situation and providing suggestions for solutions that can be followed in the management and analysis of energy.Results. The BIM approach contributed to the study of the building orientation and its reflection on thermal loads, taking into account all the factors causing this load, which can be adjusted according to any requirements or code.Conclusions. Studying the building orientation during the design stage contributes to reducing the total annual heat load by more than 20 %, and this percentage varies according to the way buildings are assembled.